Sistem Pakar Diagnosa Penyakit pada Anak Usia Satu hingga Enam Tahun Menggunakan Metode Forward Chaining - Darma Setiawan Putra; Andika Rafli; Ihsan M. Arinal; Rusnanda Resky (LPPM Politeknik Aceh Selatan, 2023)
Expert systems are stems that try to integrate human knowledge into computer systems so that computers can solve problems as usually done by professional. This expert system aims to provide early information or symptoms to parents about children's diseases so that parents can find out the diseases experienced by children. This system works by entering all symptom data into the system to be traced so as to get a diagnosis of the detected results. This system was developed with PHP and MySQL programming languages as database servers. The creation of an expert system uses the Waterfall development methodology and the reasoning method used is the forward chaining method. The author hopes that this expert system can ease parents to find early solutions to treat diseases in children.